'V' Shape A–D–A‐Type Designed Small Hole Conductors for Efficient Indoor and Outdoor Staging from Solid Dye‐Sensitized Solar Cells and Perovskite Solar Cells. Issue 8 (14th July 2021) - Prasad, Jyoti; Shao, Zhipeng; Machhi, Hiren K.; Sharma, Deep S.; Patel, Vaibhav K.; Pang, Shuping; Cui, Guanglei; Soni, Saurabh S.
Abstract : With the exploration of new building blocks, a series of small organic hole transporting materials (SOHTMs) are designed and synthesized through simple microwave irradiation and systematically investigated in solid‐state dye‐sensitized solar cells (ss‐DSCs) and perovskite solar cells (PSCs). These V‐shaped SOHTMs having A–D–A architecture are endowed with low cost, better thermal stability, and good optical and electrochemical property, which respond to low indoor light and 1 sun illumination. The SOHTMs contain dibenzothiophene (DBT) and dibenzofuran (DBF) as core donors substituted with heteroaromatic molecules like naphthalene and indole, which are coded as SPH 1–SPH 4. ss‐DSCs and PSCs with SPH 4 (with LiTFSI) as SOHTMs exhibited a power conversion efficiency (PCE) amounting to 5.2% and 15.4%, respectively, under 1 sun illumination. Moreover, the applications of ss‐DSCs and PSCs in indoor environments are studied. Due to the good match with the indoor light emitting diode (LED) source, SPH 4 delivered PCEs of 26.3% (for ss‐DSCs) and 23.9 % (for PSCs) under 1800 lux illumination, which are very close to the PCE values obtained for standard hole transporting materials (HTMs) like spiro‐OMeTAD. Thus, these new SOHTMs provide the ultimate solution for the fabrication of photovoltaic devices, resulting in superior PCE under indoor light. Abstract : Simple microwave‐assisted V‐shaped small organic hole transporting materials (SOHTMs) are designed and successfully applied as HTMs in solid‐state dye‐sensitized solar cell (ss‐DSC) and perovskite solar cells (PSC) devices. These SOHTMs are explored under low‐intensity indoor LED light and the PCEs of 26.3% and 23.9% are achieved for ss‐DSCs and PSCs, respectively, at 1800 lux intensity.